2007
DOI: 10.1007/s00455-007-9098-z
|View full text |Cite
|
Sign up to set email alerts
|

Serving Temperature Viscosity Measurements of Nectar- and Honey-Thick Liquids

Abstract: This study reports the viscosity (thickness) of nectar-and honey-thick liquids measured at a typical serving temperature. Centipoise (cP) measurements were compared for three products (two starch and one gum-based thickener) mixed with five beverages that set for three time intervals (manufacturer recommended time to thicken, 10 and 30 minutes). The serving temperature of the cold beverages was 4º C (water, apple juice, orange juice, and milk), and the hot beverage (coffee) was measured at 70º C. Statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 23 publications
3
71
2
2
Order By: Relevance
“…It is well-known that the viscosity of fluids is highly temperature dependent (Garcia et al, 2008). However, study of the viscosity of thickened fluids under different temperature conditions are limited.…”
Section: Serving Temperaturementioning
confidence: 99%
See 4 more Smart Citations
“…It is well-known that the viscosity of fluids is highly temperature dependent (Garcia et al, 2008). However, study of the viscosity of thickened fluids under different temperature conditions are limited.…”
Section: Serving Temperaturementioning
confidence: 99%
“…Subsequent to the studies noted above, Garcia et al (2008) analysed the effect of temperature on viscosity of thickened fluids by measuring the viscosity of the fluid at two different temperatures, room temperature and serving temperature, at nectar-thick and honey-thick level. It was concluded that the viscosity of the thickened fluid increases as temperature decreases for starch based thickener.…”
Section: Serving Temperaturementioning
confidence: 99%
See 3 more Smart Citations